1999
DOI: 10.1023/a:1006250301254
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The immunogenicity of a sonicated extract (SE) and of outer membrane proteins (OMP) of Salmonella enteritidis was tested in birds of about 8 weeks of age. The dose, route of vaccination and the adjuvant used varied in different groups of birds. Two vaccine doses with or without adjuvant were given parenterally or orally 3 weeks apart. OMP vaccines gave significantly higher antibody titres than SE vaccines, as indicated by ELISA. The vaccines adjuvanted with oil produced higher antibody titres than those withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Importantly, the levels of mucosal IgA responses were greater than CS NPs vaccine delivery system used in other studies. 16,18 The OMPs contain the major immunodominant proteins of Salmonella and an adjuvant-based OMPs delivered parenterally in poultry significantly increases antibody responses to Salmonella. 18 Around 500 nm size nanovaccine formulation promotes the humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the levels of mucosal IgA responses were greater than CS NPs vaccine delivery system used in other studies. 16,18 The OMPs contain the major immunodominant proteins of Salmonella and an adjuvant-based OMPs delivered parenterally in poultry significantly increases antibody responses to Salmonella. 18 Around 500 nm size nanovaccine formulation promotes the humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…17 Enriched OMPs delivered with a potent adjuvant should elicit immune response and decrease Salmonella shedding in poultry. 18 Vaccines designed with Salmonella OMPs also activate professional antigen-presenting cells (APCs) thereby inducing adaptive immunity. 19 Salmonella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Above results demonstrated that rOmpF induced a strong immune response, but conferred no significant protection against E. coli CVCC 1515 in BALB/c mice, which was consistent with previous results reported by Toobak et al (2013). Meenakshi et al referred to an irrelevance of the increased antibody level as an indicator of a protective effect against Salmonella (Meenakshi et al 1999). There are several possible reasons for lower protection in this study: (i) the characteristic of a prokaryotic expressed system cannot provide the glycosylation, which may affect the antigenicity; (ii) the native active configuration of rOmpF after denaturation and renaturation could be altered, formation of a partially folded or misfolded conformation, which may affect the immunogenicity (Dowling et al 2007); and (iii) the anti-rOmpF sera did not reach or recognize the OmpF protein on the outer membrane of live E. coli due to the presence of lipopolysaccharide (LPS), pili, flagella, and other porin proteins, which can mask the OmpF protein (Okamura et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In fish, it has been shown to induce protective immunity against Vibrio harveyi in Senegalese sole ( Solea senegalensis , Kaup) [47], E. tarda in Japanese flounder ( Paralichthys olivaceus ) [48], Vibrio anguillarum in Asian sea bass ( Lates calcarifer ) [49], and A. hydrophila in carp [11]. As pointed out by Meenakshi et al [50], OMPs are only protective in the presence of adjuvants and, hence, it is likely that the higher protection induced by the NP-rOmpA vaccine was due to the adjuvant effect of the chitosan NPs used to deliver the rOmpA antigens in this study [51]. On the contrary, the lower protection levels observed in the IWC-ET group could be due to the lack of an adjuvant that would be able to boost the immunogenicity of IWC antigens and the fact that there was possibly no depot formation for the slow release of the IWC-ET antigen.…”
Section: Discussionmentioning
confidence: 99%